Reflections on the science–policy interface within education for sustainable development in Germany. Issue 4 (3rd April 2021) - Singer-Brodowski, Mandy; Brock, Antje; Grund, Julius; de Haan, Gerhard
Abstract: While science–policy interfaces (SPIs) are argued to be crucial in developing and implementing effective public policy programmes, what happens in a particular SPI policy-research relationship remains under-researched, particularly in relation to 'success criteria' for policy makers and researchers. In this article, we address this gap by examining the SPI created for monitoring the national implementation of UNESCO's Global Action Programme for Education for Sustainable Development (ESD) policies in Germany. Our study used analytical autoethnography and intersubjective group discussions with the ESD-SPI researchers. Findings illustrate key considerations for fostering productive working relationships. These include: (i) dealing with different expectations and perspectives on measuring policy implementation; (ii) reflecting on the diverse ways an evidence base is used; and (iii) becoming more aware of and factoring in power dynamics, at the SPI. We conclude with a series of questions for further examining 'critical detachment' by researchers and 'constructive involvement' with policymakers in SPIs.